Ethnobotany of the biosphere reserve, of pantanos de Centla, Grijalva-Usumacinta basins - Magaña Alejandro, Miguel Alberto; Ramírez-Méndez, Karina de los Ángeles; Palomeque-de la Cruz, Miguel Ángel; Galindo- Alcántara, Adalberto (Ecosistemas y Recursos Agropecuarios, 2020)
Pantanos de Centla has a high diversity of plants and is a transforming source of chemical and biological materials that help stabilize water supplies. Research on plants’ use today, from a conception of environmental sciences and human knowledge, is closely related to ethnobotany, which defines the interrelationships between human groups and plants. We carried out ten surveys in each of the five communities of the Reserve (Simón Sarlat, Tres Brazos, Quintín Arauz, San José, and Los Güiros) that added up to 50 in total. Starting from lists of species from previous works, where 813 taxa were reported, plus the species found in this study, a total of 928 species were identified, of which 344 were recognized as beneficial. The family with more valuable species (36) was the Fabaceae, 12 of them with ethnobotanical use, from which the medicinal (32%), ornamental (29%), and food (19%) stand out. Of the medicinal plants, the most used parts were the leaves and fruits. Finally, 25 affections were registered, standing out the respiratory and digestive problems. Thus, it is established that the Pantanos de Centla Biosphere reserve inhabitants have a broad knowledge of plants’ use and define their processes in the transfer of this knowledge over time, so it is essential to continue with ethnobotanical research and documentation.